Civilians or Combatants? The Legal Status of Journalist in the Cambodia-Thailand Armed Conflict Under International Humanitarian Law - Vinata, Ria Tri (Faculty of Law, Universitas Jambi, 2026)
Background: Journalists covering armed conflict zones have a strategic role to play in ensuring the public's right to information and promoting accountability for violations of international law. The armed conflict between Cambodia and Thailand in the border area around Preah Vihear Temple shows that territorial disputes between developing countries can be a high-risk situation for journalists' safety. Methodology This research uses a normative legal research method with a statutory and conceptual approach. It analyses international legal instruments such as the 1949 Geneva Conventions, 1977 Additional Protocol I, international human rights instruments, and International Court of Justice judgements related to the Cambodia-Thailand dispute. In addition, the study also analyses reports from international organisations to assess the practice and implementation of journalist protection. Objective: The research aims to analyse the legal protection of journalists in interstate armed conflicts, assess the responsibilities of the Cambodian and Thai governments towards the protection of journalists, and analyse the role of ASEAN in the context of journalist protection in Southeast Asia. The findings: show that while international humanitarian law provides clear normative protection for journalists as civilians, its implementation at the national and regional levels remains weak. State responsibility is often hampered by military operational practices, while ASEAN's protection mechanisms remain normative and non-binding. Originality: This research offers an integrated analysis of international humanitarian law, state responsibility, and ASEAN regional governance in the context of interstate armed conflict in Southeast Asia, which has rarely been analysed to date